Measuring Immersion, Involvement, and Attention Focusing Tendencies in the Mediated Environment: The Applicability of the Immersive Tendencies Questionnaire - Rózsa, Sándor; Hargitai, Rita; Láng, András; Osváth, Anikó; Hupuczi, Ernő; Tamás, István; Kállai, János (Frontiers in Psychology, 2022)
This study explores the personal predispositions and dependencies while individuals use digital media and communication devices and analyses the statistical features of the Immersive Tendencies Questionnaire (ITQ) that is popular in assessing the personality trait-dependent reaction to mediated environments. The study evaluated 781 healthy graduates and postgraduates of which 192 were men (average age: 28.6 years) and 589 were women (average age: 28.4 years). We applied several questionnaires to measure immersive tendencies in a mediated environment, adaptive and maladaptive personality predispositions, and problematic Internet use and Facebook addiction scales. We analyse the statistical features of the long and short forms of the Immersive Tendencies Questionnaire. The data obtained support the reliable usage of the short form of instrument. The factor structure of questionnaire presents dual facets. First, it indicates an absorptive and immersive tendency in any case of maladaptive tendencies. Second, it reflects an intensive capability to focus on the mediated environment with adequate cognitive control to avoid any contingency of being addicted. The short form of the ITQ is reliable and adequate to assess the relationship between the self-referred and environment-dependent psychological functions.